1984
DOI: 10.2105/ajph.74.6.602
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne giardiasis at a mountain resort: evidence for acquired immunity.

Abstract: In November 1981, an outbreak of waterborne giardiasis occurred at a popular ski resort in Colorado. Stratification of illness by consumption of municipal tap water showed a striking dose-response, with an attack rate of 42 per cent among persons who drank six or more glasses of water per day. Filtered water samples revealed Giardia cysts in specimens both before and after treatment, and several deficiencies were found in the water treatment facility. Residents who had lived in the area >2 years had a lower at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 20 publications
0
34
0
1
Order By: Relevance
“…Humans with immunodeficiencies in the form of common variable immunodeficiency (CVID) and impaired IgA function have an increased risk of developing chronic Giardia infections (10,11). People living in areas where giardiasis is endemic, who are likely to have experienced numerous encounters with Giardia, are less prone to infection or reinfection, indicating that acquired immunity exists (12,13).…”
mentioning
confidence: 99%
“…Humans with immunodeficiencies in the form of common variable immunodeficiency (CVID) and impaired IgA function have an increased risk of developing chronic Giardia infections (10,11). People living in areas where giardiasis is endemic, who are likely to have experienced numerous encounters with Giardia, are less prone to infection or reinfection, indicating that acquired immunity exists (12,13).…”
mentioning
confidence: 99%
“…Cyst concentration in drinking water and parasite host specificity, infectivity, and virulence as well as population susceptibility are complex, interacting variables. Acquired immunity was noted in one study comparing attack rates of residents with those of visitors during a waterborne outbreak of giardiasis [27]. Another recent community study showed that residents with laboratory-confirmed giardiasis from one waterborne outbreak were much less likely to be infected in the second outbreak [28].…”
Section: Discussionmentioning
confidence: 99%
“…É possível que um menor percentual entre adolescentes e adultos decorra da imunidade adquirida após exposições precoces e sucessivas, resultando em infecções assintomáticas. [21][22][23] A baixa dose infectante contribui para a rápida disseminação da infecção nos países pobres, e durante surtos epidêmi-cos, nos países desenvolvidos. O cisto viável ingerido é a forma infectante sendo capaz de sobreviver em ambiente externo adequado por longos períodos.…”
Section: Giardíaseunclassified